2007
DOI: 10.1073/pnas.0706352104
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of rice-water stool from patients with Vibrio cholerae plays a role in the transmission of infectious diarrhea

Abstract: At the International Centre for Diarrhoeal Disease Research, Bangladesh, one-half of the rice-water stool samples that were culturepositive for Vibrio cholerae did not contain motile V. cholerae by standard darkfield microscopy and were defined as darkfieldnegative (DF ؊ ). We evaluated the host and microbial factors associated with DF status, as well as the impact of DF status on transmission. Viable counts of V. cholerae in DF ؊ stools were three logs lower than in DF ؉ stools, although DF ؊ and DF ؉ stools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 34 publications
3
65
1
Order By: Relevance
“…This observation can be explained by assuming that phage particles had already adhered to a proportion of V. cholerae cells, and hence, despite the dilution of stools, a considerable number of phage particles were inoculated into the mice. A recent study showed that the motility of V. cholerae cells in phage-positive cholera stools was less than that in phage-negative stools (18). We presume that the reduced motility could be due to the adherence of phage particles to the bacterial cells.…”
Section: Vol 76 2008 Effect Of Phage On Infectivity Of V Cholerae mentioning
confidence: 67%
“…This observation can be explained by assuming that phage particles had already adhered to a proportion of V. cholerae cells, and hence, despite the dilution of stools, a considerable number of phage particles were inoculated into the mice. A recent study showed that the motility of V. cholerae cells in phage-positive cholera stools was less than that in phage-negative stools (18). We presume that the reduced motility could be due to the adherence of phage particles to the bacterial cells.…”
Section: Vol 76 2008 Effect Of Phage On Infectivity Of V Cholerae mentioning
confidence: 67%
“…Interestingly, infectious V. cholerae are often taken up as small biofilms, from which bacteria escape to colonise the epithelium. Once bound to host cells, bacteria initiate microcolony formation, before eventually exiting the host's gastrointestinal tract, often following re-organisation into biofilms, 32,33 to cause environmental dispersal and onwardtransmission (Scheme 1A). The ability to transition between motile and sessile states is thus key to V. cholerae's virulence regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Spirochetes were also found in 4/11 and 5/15 samples that harbored ETEC alone or both ETEC and V. cholerae, respectively. When we removed ETEC-positive samples as potential confounders, the presence of spirochetes was independent of lytic vibriophage in V. cholerae-positive stool samples (online Technical Appendix, panel G), which is in contrast to the documented trend concerning non-V. cholerae bacteria in rice-water stool (14). The ratio of spirochetes to V. cholerae was ≈1 and independent of lytic vibriophage (online Technical Appendix, panel H).…”
Section: The Studymentioning
confidence: 89%
“…Rice-water stool samples were collected from symptomatic cholera patients (>15 years of age with no history of antimicrobial drug therapy) during the spring cholera outbreak of 2006 in Dhaka, Bangladesh, at the International Centre for Diarrheal Disease Research, Bangladesh, as part of a larger study (14). Samples were examined by dark-fi eld microscopy for V. cholerae and other bacteria, and the presence of V. cholerae, lytic vibriophage, and ETEC was determined by using standard methods (14).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation